A system dynamics model for near-miss reporting in complex systems. (October 2021) - Bugalia, Nikhil; Maemura, Yu; Ozawa, Kazumasa
Highlights: In ultra-safe systems, near-miss reporting is essential for safety. System-Dynamics (SD) modelling approach is used to model reporting behavior. Even for ultra-safe systems, trade-offs between safety and production may exist. Policies to influence worker fatigue must consider its current system state. The model developed is generalizable to systems with high predetermination. Abstract: For organizations managing ultra-safe complex systems, near-miss reports provide a valuable opportunity to improve safety. Recent academic studies have emphasized the necessity of considering the interactions among several factors influencing the reporting behavior of employees. This study develops a model of near-miss reporting behavior that considers interactions among factors such as an employee's individual characteristics and decisions by organizational management. The current study adopts a System Dynamics (SD) methodology for model development and provides an example of how modelling can be used as an organizational policy tool. A cross-industry literature review is used to develop the causal structure of the model. To evaluate the model's generalizability, the causal structure is then verified with expert interviews from two different systems, the High-Speed Railway and the construction industry. Factors common across the two near-miss reporting systems are the worker's fatigue and a positive utility of reporting. The causal structure is then converted to a simulation SD model and is calibrated to simulate the trends in the number of near-miss reports with unique data on good-observations obtained from the construction industry. The simulations were able to capture the trade-off between the number of near-miss reports and working hours. Such management policy simulations are particularly relevant for ultra-safe complex systems, and help emphasize how systems will continue to face safety-related trade-offs despite overcoming the more commonly reported trade-offs associated with tangible production losses from incidents. The discussion emphasizes that management policies to influence worker fatigue must adequately consider its current system state.